2017
DOI: 10.1136/bmjopen-2016-014911
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between dietary factors and the number of altered metabolic syndrome components in Chinese adults: a cross-sectional study using data from the China Health and Nutrition Survey

Abstract: ObjectivesTo study the correlation between dietary factors and the number of altered metabolic syndrome components (MetS) in Chinese adults systematically.SettingA cross-sectional study using demographic and dietary data of adults aged 18–75 years from the China Health and Nutrition Survey (2009) was conducted in nine provinces in China.ParticipantsThere were 6034 eligible subjects (2800 men and 3234 women) in this study.OutcomesThe primary outcome of this study were diet assessments and the number of altered … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
25
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(27 citation statements)
references
References 53 publications
(65 reference statements)
2
25
0
Order By: Relevance
“…Insulin resistance has been implicated in the development of metabolic syndrome (MetS) [9]. MetS, a highly widespread disease among developed and developing populations, is characterized by a cluster of risk factors that threatens public health and increases disability, mortality, and health-care costs [10,11]. As mentioned earlier, researches supported the notion that low intakes of dietary Mg may contribute to insulin resistance.…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…Insulin resistance has been implicated in the development of metabolic syndrome (MetS) [9]. MetS, a highly widespread disease among developed and developing populations, is characterized by a cluster of risk factors that threatens public health and increases disability, mortality, and health-care costs [10,11]. As mentioned earlier, researches supported the notion that low intakes of dietary Mg may contribute to insulin resistance.…”
Section: Introductionmentioning
confidence: 95%
“…The 2009 CHNS combined data from three consecutive days of 24-hour dietary recall and a household food inventory to assess individual consumption [10]. Individual dietary intake for three consecutive days (2 weekdays and 1 weekend day) was collected for every household member.…”
Section: Dietary Mg Intake Assessment and Other Relevant Variablesmentioning
confidence: 99%
“…Thus, there are a considerable amount of cross-sectional studies looking at both dietary intake of individuals and serum concentrations of nutrients (Li et al, 2013;Wang et al, 2008). The majority of cross-sectional studies are based on a subsample of individuals from a larger epidemiological study such as a cohort or a national health and examination survey (Wang et al, 2008;Cheng et al, 2017;Beydoun et al, 2012).…”
Section: Description Of Methods Used In Primary Researchmentioning
confidence: 99%
“…For instance, the Tehran lipid and glucose study reports nutrient intake for individuals with insulin resistance and individuals without (Mirmiran et al, 2016). Studies that report MS sometimes split participants by the number of MS components observed (Cheng et al, 2017). In these cases, individuals with insulin resistance or with the most components of MS will have a BMI of >25kg/m 2 and the controls will be individuals with no components of MS or with a BMI of <25kg/m 2 .…”
Section: Criteria For Determination Of Independent Findingsmentioning
confidence: 99%
See 1 more Smart Citation